SURFACE COMPLEXATION OF SULFATE BY HEMATITE SURFACES: FTIR AND STM OBSERVATIONS - A LEED, RHEED, AND AES STUDY - Eggleston C.M.; Hug S.; Stumm W.; Sulzberger B.; Dos Santos Afonso M. (My University, 1998)
Sulfate adsorbed to hematite surfaces from aqueous solution is examined using Fourier transform infrared (FTIR) spectroscopy and scanning tunneling microscopy (STM). FTIR was carried out using an Attenuated Total Reflectance (ATR) element coated with a fixed layer of hematite particles; this configuration allowed in situ variation of pH and sulfate concentration. The FTIR results are consistent with an inner-sphere monodentate surface complex. On dried samples, sulfate may form bidentate or possibly monodentate bisulfate complexes. STM was applied to samples that were removed from solution and imaged in air, conditions corresponding to those of the dried samples in FTIR. The images show mobile adsorbates whose lifetimes were greater than 5 ms and less than 240 ms, times that bracket the average lifetimes of aqueous FeSO4+ complexes (~50 ms). In addition, the images show pairs of bumps, in agreement with STM images of bisulfate adsorbed on Pt(111) electrode surfaces (). Although the STM images do not provide chemical identification, they are consistent with imaging of adsorbed inner-sphere sulfate (STM is incapable of seeing outer-sphere adsorbates).Our results suggest that categorization of adsorbates into inner-sphere and outer-sphere on the basis of macroscopic adsorption information is perhaps oversimplistic. Instead, a spectrum of intermediate behaviors is likely. Adsorbates classed (macroscopically) as outer-sphere may be those for which a relatively small proportion of adsorbates are in inner-sphere complexes at any given time.